Xylene delays the development of Leydig cells in pubertal rats by inducing reactive oxidative species. (30th April 2021) - Zhu, Qiqi; Zhou, Songyi; Wen, Zina; Li, Huitao; Huang, Bingwu; Chen, Yier; Li, Xiaoheng; Lin, Han; Wang, Yiyan; Ge, Ren-Shan
Graphical abstract: Illustration of the effect of xylene on Leydig cells. Xylene induces ROS, which inhibits the phosphorylation of ERK1/2 and AKT1, thereby weakening its inhibitory effect on GSK-3β through phosphorylation, resulting in the down-regulation of the genes related to steroidogenesis in Leydig cells, and ultimately reducing the synthesis of testosterone. Reduced AKT1 phosphorylation also leads to down-regulation of cyclin D and inhibition of cell proliferation. Xylene also reduces the level of SIRT1, which interacts with GSK-3β, thereby inhibiting steroid production. Abstract: Xylene is a cyclic hydrocarbon, which is commonly used as a solvent in dyes, paints, polishes, and industrial solutions. It is a potential environmental pollutant. Here, we report the effect of xylene exposure on Leydig cell development in male rats during puberty. Xylene (0, 150, 750, and 1500 mg/kg) was gavaged to 35-day-old male Sprague Dawley rats for 21 days. Xylene significantly reduced serum testosterone levels at 750 and 1500 mg/kg without affecting serum luteinizing hormone and follicle-stimulating hormone levels. Xylene reduced the number of HSD11B1-positive Leydig cells at the advanced stage at 1500 mg/kg. At 750 and 1500 mg/kg, xylene also reduced the cell size and cytoplasm size. It down-regulated the expression of Leydig cell-specific genes ( Lhcgr, Scarb1, Star, Cyp11a1, Hsd3b1, Cyp17a1, and Hsd11b1 ) and proteins. In addition, xylene significantly reduced the ratio of phosphorus-GSK-3β (pGSK-3β/GSK-3β), phosphorus-ERK1/2 (pERK)/ERK1/2, and phosphorus-AKT1 (pAKT1)/AKT1, and SIRT1 levels in the testes. In vitro Leydig cell culture showed that xylene induced oxidative stress by increasing the production of reactive oxygen species and lowing antioxidant ( Sod2 ), and inhibited the production of testosterone, and down-regulated the expression of genes related to steroidogenesis, while vitamin E reversed the xylene-mediated effect as an antioxidant. In conclusion, xylene exposure may disrupt the development of pubertal Leydig cells by increasing reactive oxygen species production and reducing the expression of GSK-3β, ERK1/2, AKT1, and SIRT1.